Exploring New Endpoints for Patients With Heart Failure With Preserved Ejection Fraction. (November 2016) - Butler, Javed; Hamo, Carine E.; Udelson, James E.; Pitt, Bertram; Yancy, Clyde; Shah, Sanjiv J.; Desvigne-Nickens, Patrice; Bernstein, Harold S.; Clark, Richard L.; Depre, Christophe; Dinh, Wilfried; Hamer, Andrew; et al.
Abstract : The epidemiological, clinical, and societal implications of the heart failure (HF) epidemic cannot be overemphasized. Approximately half of all HF patients have HF with preserved ejection fraction (HFpEF). HFpEF is largely a syndrome of the elderly, and with aging of the population, the proportion of patients with HFpEF is expected to grow. Currently, there is no drug known to improve mortality or hospitalization risk for these patients. Besides mortality and hospitalization, it is imperative to realize that patients with HFpEF have significant impairment in their functional capacity and their quality of life on a daily basis, underscoring the need for these parameters to ideally be incorporated within a regulatory pathway for drug approval. Although attempts should continue to explore therapies to reduce the risk of mortality or hospitalization for these patients, efforts should also be directed to improve other patient-centric concerns, such as functional capacity and quality of life. To initiate a dialogue about the compelling need for and the challenges in developing such alternative endpoints for patients with HFpEF, the US Food and Drug Administration on November 12, 2015, facilitated a meeting represented by clinicians, academia, industry, and regulatory agencies. This document summarizes the discussion from this meeting.